PERSEPSI DAN PARTISIPASI MASYARAKAT TERHADAP PROGRAM KELUARGA BERENCANA (Penelitian di Desa Panggungharjo, Kec. Sewon, Kab. Bantul) - Taat Wulandari * (Pendidikan Sosiologi FIS UNY, 2008)
This research’s goal is to learn on the development of the Family Planned program in the village after these years; various participations from people including village leaders (formal and non-formal), cadres and Family Planned participants, husbands and young people. Villager’s perception, which consists of viewpoint and behavior of the leaders, cadres, husbands, and the young people to the Family Planned program and its advantage in the village during these years. This research was using the method of descriptive qualitative. This research is meant to reveal various qualitative information with detail and meaningful analysis-descriptive, however does not ignore the quantitative information in the form of number nor amount. In each project will be seen the tendency, the pattern of thinking, disorder, behavior and the integration in genetic study of case. As mentioned previously, this research is using the strategy of case study. This type of strategy of with more specific details is called embedded case study research. The results of this research show that after all these years, the Family Planned program in Pangggungharjo village was routinely held and or even more has been the tradition in society; to the Family Planned program, the perception of society, leaders and also health experts are positive therefore they highly participate. However, the forms of participations are limited to their understanding of the Family Planned program. The most highly participated people are those Family Planned program’s participants themselves. While the participation of the Health Center’s officers are by serving the program, leaders and cadres are limited to invite to join and facilitate the program. The relation of perception and participation is strong mostly because of the economic, social and culture background. The characteristic of simple life also put simple behavior in their daily life. Keywords: Family Planned, Participation, Perception